2014
DOI: 10.5194/hess-18-1995-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term precipitation forecast for drought relief using atmospheric circulation factors: a study on the Maharloo Basin in Iran

Abstract: Abstract. Long-term precipitation forecasts can help to reduce drought risk through proper management of water resources. This study took the saline Maharloo Lake, which is located in the north of Persian Gulf, southern Iran, and is continuously suffering from drought disaster, as a case to investigate the relationships between climatic indices and precipitation. Cross-correlation in combination with stepwise regression technique was used to determine the best variables among 40 indices and identify the proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It is more probably because of the low fluctuation within the data during the drought periods.Since the standard deviation of data reduces during the dry months the uncertainty of forecasting reduces consequently. Throughout the long-term prediction of precipitation in Maharloo Lake Basin, south-west of Iran,Sigaroodi et al (2013) reported a similar result. They attributed low accuracy of wet months' forecast to the long distance of the case study to the Pacific and Atlantic oceans.…”
supporting
confidence: 74%
“…It is more probably because of the low fluctuation within the data during the drought periods.Since the standard deviation of data reduces during the dry months the uncertainty of forecasting reduces consequently. Throughout the long-term prediction of precipitation in Maharloo Lake Basin, south-west of Iran,Sigaroodi et al (2013) reported a similar result. They attributed low accuracy of wet months' forecast to the long distance of the case study to the Pacific and Atlantic oceans.…”
supporting
confidence: 74%
“…Among these indices, correlation of the AMO, NINO3.4 NINO4, NTA, and TNA is significant with SPI time series at the 5% level of confidence (all of the meaningful indices are related in different lag-times (Table 1) with SPI but not simultaneously). The goal of the Cross-Correlation Function (CCF) is to determine the best time lag for independent variables that have the most influence on the dependent variable (Sigaroodi et al 2013). So, we considered a MLR equation by using these significant climate indices in diffirent lag-times.…”
Section: Cross-correlation and Mlr Prediction Resultsmentioning
confidence: 99%
“…According the Sigaroodi et al (2013) This study indicated that regression model cannot predict Standard Deviation (SD) or fluctuations of observation data ( Figure 5). So, MLR is not capable enough to predict the wet years and droughts.…”
Section: Discussionmentioning
confidence: 98%
“…The Taylor diagram graphically shows how the prediction models are matched with observations in terms of correlation, their root-mean-square difference, and the ratio of their variance considered in a single diagram [82]. On this diagram, the mode that is closer to the observation (validation dataset) has the highest predictive performance [83]. The abovementioned statistical indexes can be calculated by Equations (7)-(9) as below [84]:…”
Section: Statistical Metricsmentioning
confidence: 99%